Profiling and functional analysis of differentially expressed circular RNAs in high glucose‐induced human umbilical vein endothelial cells - Jin, Guoxi (FEBS Open Bio, 2019)
Dysfunction of vascular endothelial cells often results in diabetic vascular complications. Circular RNAs (circRNAs) have been implicated in the pathogenesis of various diseases, including diabetes and many vascular diseases. This study aimed to explore the roles of circRNAs in high glucose‐induced human umbilical vein endothelial cells (HUVECs) to elucidate the contributions of circRNAs to diabetic vascular complications. We subjected control and high glucose‐induced HUVECs to RNA sequencing and identified 214 differentially expressed circRNAs (versus control HUVECs, fold change ≥ 2.0, P < 0.05). We then validated seven of these differentially expressed circRNAs by qPCR (hsa_circ_0008360, hsa_circ_0005741, hsa_circ_0003250, hsa_circ_0045462, hsa_circ_0064772, hsa_circ_0007976, and hsa_circ_0005263). A representative circRNA–microRNA (miRNA) network was constructed using the three most up‐regulated circRNAs (hsa_circ_0008360, hsa_circ_0000109, and hsa_circ_0002317) and their putative miRNA. Bioinformatic analysis indicated that these circRNAs regulate the expressions of genes involved in vascular endothelial function and angiogenesis through targeting miRNAs. Our work highlights the potential regulatory mechanisms of three crucial circRNAs in diabetes‐associated endothelial dysfunction.